(untitled) (Communications in Computational Physics, 2010)
Three-dimensional molecular dynamics (MD) simulations of gas flows con- fined within nano-scale channels are investigated by introduction of a smart wall model that drastically reduces the memory requirements of MD simulations for gas flows. The smart wall molecular dynamics (SWMD) represents three-dimensional FCC walls using only 74 wall molecules. This structure is kept in the memory and utilized for each gas molecule surface collision. Linear Couette flow of argon at Knudsen number 10 is investigated using the SWMD utilizing Lennard-Jones potential interactions. Effects of the domain size on the periodicity boundary conditions are investigated using three-dimensional simulations. Domain sizes that are one mean-free-path long in the periodic dimensions are sufficient to obtain domain-size independent MD solutions of nano-scale confined gas flows. Comparisons between the two- and three-dimensional simulations show the inadequacy of two-dimensional MD results. Three-dimensional SWMD simulations have shown significant deviations of the velocity profile and gas density from the kinetic theory based predictions within the force penetration region of the walls.